Cuckoo [videorecording (Blu-Ray)] - Singer, Tilman; Schafer, Hunter, 1998-; Bluthardt, Jan; Csokas, Marton, 1966-; Henwick, Jessica, 1992-; Stevens, Dan, 1982- (Decal Releasing, LLC, 2024)
Gretchen leaves America to live with her father, who has moved to the German Alps with his new family. After arriving, Gretchen is plagued by strange noises and bloody visions until she discovers a shocking secret about her own family.